Faktor-faktor yang memengaruhi pengungkapan tanggung jawab sosial perusahaan - Wandriani, Ike Putri (Jurnal Manajemen Bisnis dan Kewirausahaan, 2017)
The purpose of this research is to provide empirical evidence on whether firm size, profitability, size of audit firm, leverage, net profit margin, and liquidity influence corporate social responsibility disclosure. This research used 60 samples of companies in the manufacturing sector that had been listed on the Indonesian Stock Exchange, within the period from 2011 until 2013. Sample were obtained by purposive sampling method. Data were analyzed using the multiple regression method. The result of this research showed that firm size, leverage, and net profit margin influenced corporate social responsibility disclosure. On the contrary, profitability, size of the audit firm, and liquidity did not influence corporate social responsibility disclosure.